THEOLOGICAL REFLECTION OF SARTRE'S THEATER PLAY THE DEVIL AND GOD - Provazník, David (Bohemica Olomucensia, 2021)
The study focuses on the interpretation of the play J.-P. Sartre The Devil and God. The primary goal is to describe the contrast between existentialism and Christianity, as it is a game in which these currents of thought collide with each other. The structure of the work consists of four basic points. First, Sartre and atheism. Second, the concept of existence and its ontological concept. Third, the theoretical concept of literature and the classification of plays. Fourth interpretation of the chosen theater play and its theological reflection.
Keywords: Jean-Paul Sartre; The Devil and God; theater play; existentialism; interpretation; theology